CRS 111 - Basic Coding 1 - Linn Benton Virtual College (2018)
This course prepares the medical coding student for detailed procedural coding in integumentary, musculoskeletal, respiratory, and cardiovascular systems. Additionally, this course prepares the student to use ICD-10 diagnostic codes as principal, primary, secondary, and tertiary medical necessity justification. This course also prepares students to competently select accurate HCPCS codes for supplies, medications, transportation, etc.